2000
DOI: 10.1046/j.1365-2109.2000.00496.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of environmental factors, depth and position on the growth and mortality of raft-cultured blue mussels (Mytilus edulis L.)

Abstract: One‐year‐old rope grown blue mussels (Mytilus edulis L.) were grown in experimental lantern nets at two depths (2 and 6 m below the surface) in two different positions (inflow and outflow) off a raft in Loch Etive on the west coast of Scotland. Shell and tissue growth, and mortality were recorded. Water temperature, salinity and food availability were also monitored over the experimental period. There were no significant differences in the length, live weight, wet meat weight, dry meat weight and ash‐free dry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 14 publications
(21 reference statements)
2
18
2
Order By: Relevance
“…A variety of environmental factors are known to influence shell morphology and the relative proportions of many bivalve species (Gaspar et al 2002). For examples, the type and quality of phytoplankton as a food source of the mussels (Kovitvadhi et al 2006;Alunno-Bruscia et al 2001), water quality (Lajtner et al 2004;Buddensiek 1995), water depth (Claxton et al 1998;Karayücel andKarayücel 2000, Lajtner et al 2004), currents (Blay 1989;Fuiman et al 1999), water turbulence (Hinch and Bailey 1988), type of sediment (Newell and Hidu 1982;Lajtner et al 2004), type of bottom (Claxton et al 1998) and wave exposure (Akester and Martel 2000). Buddensiek (1995) described the culture of juvenile Margaritifera margaritifera in cages as a useful method of raising the early post-parasitic stages in four suitable rivers.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of environmental factors are known to influence shell morphology and the relative proportions of many bivalve species (Gaspar et al 2002). For examples, the type and quality of phytoplankton as a food source of the mussels (Kovitvadhi et al 2006;Alunno-Bruscia et al 2001), water quality (Lajtner et al 2004;Buddensiek 1995), water depth (Claxton et al 1998;Karayücel andKarayücel 2000, Lajtner et al 2004), currents (Blay 1989;Fuiman et al 1999), water turbulence (Hinch and Bailey 1988), type of sediment (Newell and Hidu 1982;Lajtner et al 2004), type of bottom (Claxton et al 1998) and wave exposure (Akester and Martel 2000). Buddensiek (1995) described the culture of juvenile Margaritifera margaritifera in cages as a useful method of raising the early post-parasitic stages in four suitable rivers.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Loch Etive in the 1990s did not report any unusual mussels (Okomus and Stirling 1998;Karayucel and Karayucel 2000). Mussels sampled from Loch Etive in 1999 were used as a reference population of presumed pure M. edulis by Wood et al (2003), and the same genetic markers Me 15/16 identified all samples to be M. edulis homozygotes.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality was clearly lower (5%) than the other sites' cultured mussels, M. galloprovincialis . Mortality is variable and depends on mussel species (<2% for M. edulis and M. galloprovincialis in Galicia, Camacho et al (1995); between 12.57% and 14.03% for M. edulis in Loch Etive, Scotland, Karayücel & Karayücel 2000), seed sources (10.715% and 23.38%, several Galician stocks and culture in three sites Ria de Arousa, Fuentes, Reyero, Zapata & Alvarez 1994), different environmental conditions (8.00% and 26.67% in different estuaries in Galicia, Villalba, Mourelle, Carballal, López & Azevedo 1993) and culture systems (22.14% and 25.92% in rocky shore and collector ropes, Fuentes et al 1998). Fuentes et al (1992) reported that mortality was <4.5% in raft culture at the three culture sites in Galicia between May and August.…”
Section: Discussionmentioning
confidence: 99%